Structure-Guided Combinatorial Engineering Facilitates Affinity and Specificity Optimization of Anti-CD81 Antibodies. Issue 14 (6th July 2018) - Nelson, Bryce; Adams, Jarrett; Kuglstatter, Andreas; Li, Zhijian; Harris, Seth F.; Liu, Yang; Bohini, Sandya; Ma, Han; Klumpp, Klaus; Gao, Junjun; Sidhu, Sachdev S.
Abstract: Hepatitis C viral infection is the major cause of chronic hepatitis that affects as many as 71 million people worldwide. Rather than target the rapidly shifting viruses and their numerous serotypes, four independent antibodies were made to target the host antigen CD81 and were shown to block hepatitis C viral entry. The single-chain variable fragment of each antibody was crystallized in complex with the CD81 large extracellular loop in order to guide affinity maturation of two distinct antibodies by phage display. Affinity maturation of antibodies using phage display has proven to be critical to therapeutic antibody development and typically involves modification of the paratope for increased affinity, improved specificity, enhanced stability or a combination of these traits. One antibody was engineered for increased affinity for human CD81 large extracellular loop that equated to increased efficacy, while the second antibody was engineered for cross-reactivity with cynomolgus CD81 to facilitate animal model testing. The use of structures to guide affinity maturation library design demonstrates the utility of combining structural analysis with phage display technologies. Graphical abstract: Unlabelled Image Highlights: We solved crystal structures of four single-chain variable fragments in complex with the CD81 large extracellular loop We combined structural analysis to guide library design for affinity and specificity optimization of two of these antibodies We engineered one antibody for increased affinity We engineered one antibody for species cross-reactivity Mode of inhibition of hepatitis C virus entry via CD81 was determined